Tailoring treatment for elderly bladder cancer: a case report of personalized management of high-grade urothelial carcinoma with papillary features - Nikolaidis, Christos G.; Gyriki, Despoina; Anitsakis, Charalambos; Stavropoulou, Elisavet (Frontiers in Oncology, 2024)
This case study presents the diagnostic and therapeutic course of a 72-year-old male patient with a history of high-grade urothelial carcinoma with papillary features. The report outlines the patient's initial presentation, the intervention strategies employed, including transurethral resection and intravesical Bacillus Calmette-Guérin (BCG) therapy, the subsequent complications and clinical decisions following the intense symptoms post-treatment. The study highlights the challenges in managing bladder cancer in elderly patients, considering the tumor's characteristics, treatment responses, and the patient's quality of life.